The Multiplier-Effects of Non-Wasteful Government Expenditure - Luigi Marattin; Massimiliano Marzo (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2010)
Macroeconomic literature has traditionally regarded public expenditure as yielding no utility per se to any agent in the economy. In line with a few previous contributions (Linneman and Schabert 2004, Bouakez and Rebei 2007) we build a New Keynesian DSGE model with real and nominal rigidities and distortionary fiscal policy rules, calibrated on the Euro-area (1990:Q1-2008:Q4), where part of public spending is allowed to either Edgeworth complement or substitute private consumption by affecting its marginal utility. We show that the the interaction between the share of usefulness of public spending and the specification of fiscal and monetary policy rules is able to deliver private consumption multipliers which are in line with the empirical findings for the Euro-Area.
Keywords: E62; E63; 330